2008
DOI: 10.1590/2175-7860200859417
|View full text |Cite
|
Sign up to set email alerts
|

Meriania (Melastomataceae; Merianieae) No Rio De Janeiro, Brasil

Abstract: RESUMO Apresenta-se o estudo taxonômico do gênero Meriania no Rio de Janeiro, com chave para identificação das espécies, descrições, ilustrações e comentários sobre distribuição geográfica e afinidades, bem como novos sinônimos. O gênero está representado por oito espécies, todas encontradas em formações de mata atlântica de altitude: M. claussenii, M. excelsa, M. glabra, M. glazioviana, M. longipes, M. paniculata, M. robusta e Meriania sp., uma nova espécie recentemente coletada no sul do estado. Excetuando-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 4 publications
(4 reference statements)
0
8
0
4
Order By: Relevance
“…These species form a coherent group, and all of them have anthers with a dorsal appendage that is elongated upwards (Chiavegatto & Baumgratz 2008). Of the seven taxa studied in the present work, only M. urceolata occurs in Amazon Forest, while all of the other species are endemic to the Atlantic Forest biome.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…These species form a coherent group, and all of them have anthers with a dorsal appendage that is elongated upwards (Chiavegatto & Baumgratz 2008). Of the seven taxa studied in the present work, only M. urceolata occurs in Amazon Forest, while all of the other species are endemic to the Atlantic Forest biome.…”
Section: Introductionmentioning
confidence: 74%
“…Other morphological characteristics also support this new synonymy, such as leaves with sinuous margins and five acrodromous suprabasal veins, a similar-shaped foliar base, the presence of domatia, floral parts of the same size, a truncate unilobate calyx with aestivation inconspicuously valvar and laciniae reduced to a sinuous sheet. Additionally, based on collections of M. paniculata from São Paulo State, the geographical distribution of this species is larger than previously thought, as Chiavegatto & Baumgratz (2008) indicated that it was endemic to Rio de Janeiro State.…”
Section: Meriania Calophyllamentioning
confidence: 82%
See 1 more Smart Citation
“…Meriania glabra é endêmica do Estado do Rio de Janeiro (Chiavegatto 2012) e ameaçada de extinção, segundo Chiavegatto & Baumgratz (2008). No PEPB é diferenciada das demais Melastomataceae pela morfologia do estame com apêndice ascendente dorsal no conectivo, sendo a única espécie pertencente à tribo Merianieae.…”
Section: Methodsunclassified
“…The fruits are of the velatidium type, polyspermic, 3-5-valved, with seeds laterally flattened, obtriangular, rarely oblong or narrowclavate, short-rostrate at the apex (Baumgratz 1985;Chiavegatto and Baumgratz 2008;Chiavegatto 2009). …”
mentioning
confidence: 99%